Optimal adaptation and mitigation to climate change in small environmental economies - Omar Chisari; Sebastián Galiani; Sebastián Miller (Inter-American Development Bank (IDB), 2013)
This paper compares the optimal dynamic choices between policies of mitigation and adaptation for three economies: Brazil, Chile and the United States. The focus is on the optimal role of mitigation and adaptation for 'environmentally small economies,' i.e., economies that are witnessing an exogenous increase in emissions to which they are contributing very little. The simulations lead to three main conclusions. First, small economies should concentrate their environmental efforts, if any, on adaptation. This is not a recommendation that such economies indulge in free-riding. Instead, it is based on considerations of cost effectiveness, ceteris paribus. Second, small economies that are unable to spend enough on adaptation may end up spending less on mitigation owing to their impoverishment as a result of negative climate shocks. Third, higher mitigation expenditures may arise not only as a result of greater optimal adaptation expenditures, but also because of increased adaptation to the incentives for mitigation provided by richer countries.
hdl:11319/4668
Keywords: Q52; Q54; 330; Optimal mitigation and adaptation policies; Environmentally small economies